Equilibrium Sedimentation of Turnip Yellow Mosaic Virus - McGee, J. H. (1974)
Sedimentation equilibrium was achieved with turnip yellow mosaic virus at low speeds (600 rpm) in a magnetic ultracentrifuge. The experiments were carried out in the newly installed constant-speed rotor, equipped with automatic control and an electromagnetic drive. A particle mass of 5.55 × 10(6) daltons was calculated for the virus at vanishing concentrations, in essential agreement with the earlier results using the more tedious procedure with a freely coasting rotor. In order to interpret the observed departure from ideal behavior (nonassociating conditions), preferential interaction experiments were carried out by magnetic densimetry. These showed that a strong Donnan effect exists at pH 7, which contributed > 10(3) times more to the nonideality than did the excluded volume effect. A net negative charge of about 3.5 × 10(3) per particle was estimated at this pH.